Pengembangan Keterampilan Warga Binaan Panti Pelayanan Sosial PGOT Mardi Utomo melalui Pendampingan Pembuatan Kue Pukis dan Perhitungan Harga Pokok : Penelitian - Putri, Alvianita Gunawan; Ardiansah, M. Noor; Hidayati, Ulfah; Murtiasri, Eka; Murtini, Sri; Asrori, Muhammad; Raharjanti, Rani; Eviyanti, Novitasari; Haris, Moh.; Mansur, Ahmad Wafa (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The PGOT Mardi Utomo Social Service Center is a social rehabilitation institution for beggars, homeless people, and abandoned people that focuses on increasing independence through skills training, but still faces obstacles such as low motivation of inmates, limited facilities, lack of understanding of business management, and inaccurate calculation of cost of goods produced (HPP). This community service activity aims to improve the skills of inmates through mentoring in making pukis cakes and training in calculating HPP as the basis for a simple culinary business. The implementation method includes needs identification, technical training, learning the concept of HPP, entrepreneurial motivation, production practice, and evaluation. The results of the activity show a significant increase in pukis cake production skills and the ability of inmates to calculate HPP independently to determine a rational selling price. This program also increases entrepreneurial motivation and opens up opportunities for economic independence, making it effective as a model for sustainable social empowerment.